The radical religious extremism offender's family rehabilitation: A proposal of designing the information technology portal - Fadzli, Adam; Najihah, Abd Wahid; Fakhratu Naimah, Muhad (IAEME Publication, 2019)
The rehabilitation approach is endorsed by the experts for its efficiency and practicality in reintegrating the radical religious extremism offenders. Other than the provided syllabus for the offenders, the rehabilitation for the family members is needed as well. However, the restriction to access the families of the offenders are obstructing the rehabilitation processes from their side. Hence, this research is proposing a special informative online portal. The advancement of the information technology (IT) application is considered to be as the easiest medium to bridge between them. This research is a qualitative study and mainly benefit from the previous research papers. This article is considered to be the first milestone in preparing the extensive and complete rehabilitation of the families of the RRE offenders cum spreading the right information to the global masses.